Captive Breeding and Rehabilitation of Mugger Crocodile (Crocodylus palustris) in Similipal Tiger Reserve, Orissa, India - Sagar, S. R.; Singh, L. A. K (Indian Forester, 1993)
Crocodylus palustris was considered to be extinct in the perennial waters of Similipal Tiger Reserve by 1980. The terrestrial and aquatic habitats, encompassing an area of 2750 km2, are under active conservation management since 1973 under Project Tiger. Between April 1981 and February 1990 a total of 238 captive reared juvenile muggers have been released in the reserve. Out of 99 muggers released during 1981-1987 in river Budhabalanga, 12.1% excluding wild-bred hatchlings are seen at present. In river West Deo 34.7% of 72 released (during 1985-1988) and wild-bred hatchling muggers are seen. In river Khairi, where releases have been made since April 1989, 71.6% are seen when reports last came in. During a thorough monitoring over 44 weeks, out of 25 muggers released at Ransaguda in river Khairi 16 young ones could still be seen within a stretch 900 m upstream and 1400 m downstream the point of release. During the monsoon, sightings were from 1 to 3 muggers. The future plan for mugger include . (i) last release in January 1991, (ii) regular monitoring of the populations in the wild, (iii) continuation of the captive breeding unit at Ramtirtha for research, education and supply of captive reared juveniles for restocking elsewhere.